Changes and Shifts In The Meaning of The Indonesian Language In The Gen-Z Youth Community - Lita Agustiana; Tiara Yuliani Sabilah; Yusida Gloriani; Komarudin Komarudin (Asian Journal of Social and Humanities, 2024)
The phenomenon of communication on social media Instagram and Tiktok in the Gen-z youth community is one of which has changed the meaning of language. Changes in meaning include expansion, narrowing, total change, refinement, and marketing. Therefore, the purpose of this study is to find out the changes and shifts in the meaning of the Indonesian language in the Gen-Z youth community and to find out what words have undergone changes and shifts in the meaning of the Gen-Z youth community on Instagram and TikTok social media. The data sources used in this study are words found on Instagram and TikTok in the Gen-Z youth community. The research method used is qualitative descriptive with the technique of reading and taking notes. The results of this study show that the meaning of language in the communication of the Gen-Z adolescent community has changed and shifted in meaning along with the development of language and technology on social media. As well as finding words that have undergone changes and shifts in the GeN-Z youth community, including; The broad meaning is; major, sultan, viral, operation, caste, stealing, and adhan, the meaning of narrowing is: teacher, revocation, and hijab, total change, namely: crisp, chili-cabean (chili), honey, change, filter, and stone, meaning of garnish, namely: dajjal, demon, and tadpole, and the meaning of refinement, namely: to the back and anjay.